2021
DOI: 10.1186/s40814-021-00943-8
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Very preterm infants engage in an intervention to train their control of attention: results from the feasibility study of the attention control training (ACT) randomised trial

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…infants’ soothing in response to parental talking). Parents were not told whether their child was receiving the treatment or the active control procedure, and the results we reported in a previous paper [ 37 , 38 ] showed that parents did not accurately guess in which group their child had been allocated: we thus argue it is unlikely that parental ratings were biased by their awareness of group allocation. Overall, these findings suggest treated infants being able to focus attention during their interactions with the environment.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…infants’ soothing in response to parental talking). Parents were not told whether their child was receiving the treatment or the active control procedure, and the results we reported in a previous paper [ 37 , 38 ] showed that parents did not accurately guess in which group their child had been allocated: we thus argue it is unlikely that parental ratings were biased by their awareness of group allocation. Overall, these findings suggest treated infants being able to focus attention during their interactions with the environment.…”
Section: Discussionmentioning
confidence: 80%
“…This is the first study that trained VP infants’ attention control. Previous analyses indicated it is possible to recruit and retain VP infants and engage them in the training [ 37 , 38 ]. Conversely, the analyses of infants’ performance in different tasks presented in this paper are important in providing initial estimates concerning the potential for improving early key cognitive abilities of this at-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations